Odpowiedź:
[tex]a) \: (x + 7)(2x - 1) = 2 {x}^{2} - x + 14x - 7 = 2 {x}^{2} + 13x - 7[/tex]
[tex]b) \: (2a - 1)(a + 4) = 2 {a}^{2} + 8a - a - 4 = 2a {}^{2} + 7a - 4[/tex]
[tex]c)(4a - 1)(2 - 3a) = 8a - 12a {}^{2} - 2 + 3a = 11a - 12 {a}^{2} - 2 = 12a {}^{2} + 11a - 2[/tex]
[tex]d)( {a}^{5} - 1)(a + 1) = a {}^{6} + a {}^{5} - a[/tex]
[tex]e)(2k {}^{2} - 1)(2k + 1) = 4k {}^{3} + 2k {}^{2} - 2k[/tex]
[tex]f)(3 - p {}^{3} )(p {}^{2} + 1) = 3 {p}^{2} + 3 - p {}^{5} - p {}^{3} = p {}^{5} - p {}^{3} + 3p {}^{2} + 3[/tex]
Szczegółowe wyjaśnienie:
nie jestem pewna czy wszystko jest dobrze